PEMANFAATAN BAKTERI SELULOLITIK DAN BAKTERI PENAMBAT NITROGEN UNTUK DEKOMPOSISI LIMBAH PERTANIAN - . Adriani; Andi Taskirah (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2014)
Agricultural waste is a byproduct of agricultural products that can be used as compost. Several studies have shown that some types of microorganisms can be utilized for agricultural waste decomposition.the combination of cellulolytic bacteria with other bacteria have been carried out for the composition process. The research methods include isolation stages cellulolytic bacteria and nitrogen-fixing bacteria , the selection of potential isolates and application on agricultural waste . The success of decomposition in terms of several parameters , among which is the C / N ratio , pH , levels of C - total and total-N . Analysis of C - organic decomposition levels were analyzed using Walkley and Black , as well as N - total with Micro Kjehdahl method . The results showed the treatment combination of cellulolytic bacteria and nitrogen-fixing bacteria give better results in the decomposition of agricultural wastes